P511 Radiological outcomes in perianal fistulising Crohn's disease. (25th January 2019) - Lee, T; Kamm, M; Bell, S; Lust, M; Brown, S; Wright, E; Connell, W; Yong, E; Ding, N
Abstract: Background: Perianal fistulas are a common and clinically challenging manifestation of Crohn's disease, affecting approximately a third of Crohn's patients. 1 While the use of biologic therapy has led to improvements in patient outcomes, loss of response is common, with subsequent worsening of fistula tracts and new abscess formation. 2 Previous studies suggest that patients who achieve deeper healing, and eradication of the tract radiologically, have longer duration of response. 3 The aim of this study was to compare the clinical course of patients achieving MRI healing with those achieving clinical remission, with the hypothesis that radiological healing will lead to a longer duration of response. Methods: A retrospective analysis of perianal fistulising Crohn's patients treated at St Vincent's Hospital, Melbourne was performed. Records were reviewed for patient demographics, disease history, clinical assessments (including PDAI scores), investigation results (including MRI pelvises), and disease flares. Clinical remission was defined as closure of all baseline fistula openings, on examination. Radiological healing was defined as the absence of any T2-hyperintense sinuses, tracts or collections. Primary endpoint was flare-free time, defined as time between achieving healing (clinical or radiological) and a patient's first signs or symptoms requiring escalation in medical and/or surgical therapy. Statistical analysis consisted of Mann–Whitney U tests, Wilcoxon Signed Rank, and Log-rank tests. Significant parameters were entered into a multi-variate Cox regression model. Results: 93 patients were included, with a median follow-up of 4.75 years (IQR, 2.4–6 years). 85/93 (91%) received treatment with a biologic agent. PDAI and van Assche scores were significantly lower following biologic treatment. Twenty-two/44 (50)% of patients achieved clinical remission, while 15/93 (16%) achieved radiological healing. Ten/22 (45%) of patients with clinical remission had a subsequent disease flare, at a median of 7 months, compared with the 3/15 (20%) patients with MRI healing, who flared at a median of 3.6 years. Radiological healing was associated with a significantly longer flare-free period ( p = 0.01). Conclusions: Radiological healing is a less common, but deeper form of healing, associated with improved clinical outcomes. Further prospective trials are required to assess the benefit of earlier, and more regular imaging, with escalation of therapy based on radiological findings. References 1. Hellers G, Bergstrand O, Ewerth S, et al . Occurrence and outcome after primary treatment of anal fistulae in Crohn's disease. Gut 1980;21:525–7 2. Sands B, Anderson F, Bernstein C, et al . Infliximab maintenance therapy for fistulizing Crohn's disease. N Eng J Med 2004;350:876–85. 3. Tozer P, Ng SC, Siddiqui MR, et al. Long-term MRI-guided combined anti-TNF-alpha and thiopurine therapy for Crohn's perianal fistulas. Inflam Bowel Dis 2012;18:1825–34.